The socialist awakening : what's different now about the left - Judis, John B (Columbia Global Reports, 2020)
"There is renewed interest in socialism in the US and the UK, particularly among young people. Who are these new socialists? Why now? THE SOCIALIST AWAKENING explores how socialism has re-entered the political mainstream and transformed the center-left across the Atlantic, driven by a rising anti-capitalist resentment among those who seek government intervention in economic equality, education, health care, and climate change. John Judis chronicles the current surge of socialist outrage-how it started, and where it is going"--